Multi-energy Domain Dynamics Full Solution Modeling and Experiment of Delta 3D Printer - Huang Kai; Guo Fei; Wang Leilei; Cui Guohua (Jixie chuandong)
This research focuses on the dynamic modeling of Delta 3D printer multi-energy domain mechanical-electrical coupling system. Based on the advantages of screw bond graph in the dynamic modeling of parallel robot，the dynamic model of the printer's mechanical ontology subsystem is constructed，and the dynamic model of the driving subsystem is established by combining with the traditional bond graph，and the global dynamic model of the printer's mechanical-electrical coupling is obtained. For a given moving platform trajectory，comparing the results of Adams numerical simulation，Matlab theoretical calculation and experimental driving force measurement show that the full solution model of multi-energy domain system dynamics of the mechanism is correct. The results lay a foundation for the following dynamic parameter identification and dynamic control research，and also provide a new idea for other mechanical system dynamics modeling.